4, 6-Dimethyl-2-mercaptopyrimidine as a potential leveler for microvia filling with electroplating copper. Issue 64 (18th August 2017) - Tang, Mingxing; Zhang, Shengtao; Qiang, Yujie; Chen, Shijin; Luo, Li; Gao, Jingyao; Feng, Li; Qin, Zhongjian
Abstract : Filling performance of microvia was defined as following equation: η = ( A / B ) × 100%. Abstract : The impact of 4, 6-dimethyl-2-mercaptopyrimidine (DMP) as a potential leveler on microvia electroplating copper filling from an acid cupric sulfate electrolyte, including polyethylene glycol (PEG), bis(3-sulfopropyl)disulfide (SPS), and chloride ion, was investigated. The results of electrochemical measurement, atomic force microscope (AFM), and X-ray photoelectron spectra (XPS) revealed that DMP adsorption on the copper surface inhibited copper deposition. Different surface morphology and crystalline orientation was observed after plating using electroplating solutions with different concentrations of DMP. Analytical data were obtained by field emission scanning electron microscope (FE-SEM) and X-ray diffractometer (XRD), respectively. In addition, quantum chemical calculations and molecular dynamics (MD) simulations were used to investigate the interaction mechanism between DMP and copper.